Description of dental caries on mixed dentition stage of elementary school students in Cibeber Community Health Center - Supriatna, Andi; Fadillah, Rina Putri Noer; Nawawi, Azkya Patria (Universitas Padjadjaran, 2017)
Introduction: Dental and oral health can affect the quality of life as it relates to the general health condition. Dental and oral health problem that mostly found is dental caries. Dental caries mostly occurs in children in the mixed dentition stage. The mixed dentition stage occurs in elementary school-aged children, mark with malocclusions and tooth decays, that allows food retention as main cause of dental caries. The purpose of this study was to see the description of dental caries on mixed dentition stage of elementary school students in Cibeber Community Health Center. Methods: This research was a descriptive research with cross-sectional approach. The population in this study was elementary school students in Cibeber Community Health Center. The sampling method used was purposive sampling method. The caries profile was measured by deft index for deciduous teeth and DMFT index for permanent teeth were presented in tabular and diagrams. Results: The results of the study towards 272 elementary school students showed that the average value of deft index was 3.99 and DMFT index value was 1.26. This result can be caused since the location of the population was located in urban areas, with easy access to dental and oral health services and good tendencies towards the awareness of dental and oral health care. Conclusion: Dental caries of elementary school students in Cibeber Community Health Center based on (World Health Organization) guidelines by deft index was category as moderate and by DMFT index was classified low category.